Componential Analysis of Meaning on Lexemes Denoting the Act of Seeing in Arabic - Zulfikri, Zulfikri (Albariq: Jurnal Pendidikan Bahasa Arab, 2022)
This research aims to find the differences in components of meaning on lexemes denoting the act of seeing in the Arabic language. Through semantics study, the analysis employs Nida’s componential analysis of meaning to figure out the distinguishing features among lexemes. This research used a qualitative method that includes the step of data collection by looking at the lexemes denoting the act of seeing from textbooks and dictionaries. The data analysis includes filtering the lexemes and analyzing the components of meaning in each lexeme by adding semantic notations to semantic features in each lexeme. The differences in components of meaning are determined by several semantic features such as the device of seeing, the way of seeing, the object, and the feeling through the process of seeing.